Use of left ventricular support devices during transcatheter aortic valve replacement and balloon aortic valvuloplasty: a single center experience. (14th October 2021) - Mahmood, S; Gelovani, D; Nona, P; Lemor, A; Basir, M; Frisoli, T; Lee, J; Wang, D; O'Neill, B; Eng, M; O'Neill, W; Villablanca, P
Abstract: Background: Transcatheter aortic valve replacement (TAVR) and balloon aortic valvuloplasty (BAV) are definitive and bridging therapies in patients with aortic stenosis. Data on utilization of mechanical circulatory support (MCS) in this population is scarce. This study sought to evaluate the clinical outcomes of the use of Impella (Abiomed, Danvers, MA) in patients undergoing TAVR or BAV at a tertiary-care center. Methods: We reviewed all TAVRs and BAVs that required Impella from 2012 and 2020. Patient demographics, procedural outcomes, complications, and 30-day mortality were analyzed. Results: A total of 1, 965 TAVR and 715 BAV cases were performed in the study period. 30 TAVR and 94 BAV cases required an Impella. 65% of these cases were due to cardiogenic shock (CS) (100% of TAVR and 55% of BAV). 31% were performed in female patients. Transfemoral access was utilized in 98% of cases. Impella CP was used in 98% of cases, other types of MCS were used in 8.7% of cases. 32.2% of cases required MCS for more than 24 hours. In the TAVR population the indication for MCS was 46.6% profound hypotension post valve deployment requiring vasopressors, 16.6% cardiac arrest, 10% sustained ventricular arrhythmia, 10% cardiac tamponade [Office1] and 10% coronary occlusion. In the BAV group the indication was 44% high-risk PCI and 56% CS. The 30-day mortality in TAVR was 40% and 28% in BAV; from the BAV group in CS the mortality was 45%. VARC-2 vascular complications and bleeding complications were observed in 4.8% and 1.5%, respectively. 0.7% of the total cohort required conversion to open-heart surgery. Conclusions: Impella support is required in a minority of TAVR or BAV cases. In those who require MCS with Impella for either BAV or TAVR, the total mortality remains high especially in those experiencing CS. Funding Acknowledgement: Type of funding sources: None.